The Genetics of Differential Gene Expression Related to Fruit Traits in Strawberry (Fragaria ×ananassa) - Barbey, Christopher; Hogshead, Max; Schwartz, Anne E.; Mourad, Nadia; Verma, Sujeet; Lee, Seonghee; Whitaker, Vance M.; Folta, Kevin M. (Frontiers in Genetics, 2020)
Octoploid strawberry (Fragaria ×ananassa) is a major specialty crop under intense annual selection for traits relating to plant vigor and fruit quality. Most functional validation experiments rely on transgenic or transient gene expression assays in the mature receptacle. These findings are not typically translatable to breeding without identifying a natural genetic source of transcript level variation, and developing reliable markers for selection in octoploids. Expression QTL (eQTL) analysis is a genetic/transcriptomic association approach for identifying sequence variants predicting differential expression. This eQTL study analyzed a wide array of mature receptacle-expressed genes, encompassing the majority of total mature receptacle transcript accumulation and almost all strawberry genes described in the literature. These results identified segregating genetic variants associated with the differential expression of hundreds of strawberry genes, many with known interest to breeders. Several of these eQTL pertain to published genes whose expression levels have been demonstrated to influence mature receptacle phenotypes. Many include key genes of the phenylpropanoid pathway, vitamin C, carotenoid, and pectin, and receptacle carbohydrate/sugar metabolism. These subgenome-specific genetic markers may allow breeders to select for desired ranges of target gene expression. These results may also guide basic research efforts and facilitate the identification of causal genes underlying trait QTL.